The Influence of Sea Water Immersion on the Mechanical Properties and Structure of Carbon Fiber/Polyester-PEG Composite Materials - Prakoso, Bagas; Pujianto, Andreas; Saharuddin, Saharuddin; Sirait, Egbert Josua; Yaqin, Rizqi Ilmal; Siahaan, Juniawan Preston; Fakhrudi, Yoga Ahdiat (Universitas Muhammadiyah Yogyakarta, 2025)
Structural batteries are a crucial solution in dealing with issues related to vehicle electrification to achieve energy sustainability in the future. However, the development of structural battery technology for electric-powered ships is still very limited. In particular, there are limitations in evaluating the mechanical performance of carbon fiber/polyester-PEG based composite materials for structural battery applications in electrically powered vessels. The main focus of this research is to fabricate carbon fiber/polyester-PEG to further observe the performance of its mechanical properties and structure when interacting with sea water. The value of the addition of polyethylene glycol (PEG) to the fabrication carried out was varied by 0%, 10%, and 25%. The results show that addition of 10% PEG produces a composite with the highest tensile strength, increasing the toughness of the polyester material. However, all samples experienced a decrease in tensile strength after immersion due to decreased bond performance between the fibers and seawater. The addition of 25% PEG resulted in a significant decrease in mechanical properties because high levels of PEG content made the sample easily brittle and destroyed when interacting with seawater. This research can provide initial studies on the development of carbon fiber/polyester-PEG composite materials that can be used as structural battery building materials for future electric boat applications.